Design, Implementation and Evaluation of an Emotional Education Program: Effects on Academic Performance - Mira-Galvañ, María-José; Gilar-Corbi, Raquel (Frontiers in Psychology, 2020)
Background: In recent decades, the amount of research on social and emotional learning programs in schools has increased significantly, showing a great number of positive student outcomes, including greater ability to perceive, understand and manage emotions, better attitudes about self and others, less aggressive and/or disruptive behavior, higher levels of psychological well-being and improvement in academic performance among others. The purpose of this research was the design and implementation of the OKAPI emotional education program. A multidimensional program based on cooperative learning methodology. Methods: 86 students of Primary Education, from 3rd to 5th grade (45 students in the experimental unit and 41 in the control group). Results: The implementation of the OKAPI has a positive impact in academic achievement. Conclusion: This program shows the convenience of incorporating programs that can be integrated into the school life and can be applied by the teaching staff using both social emotional learning and school climate approaches.